Force Characteristics of Sluice Structure in Coastal Area Under Wind Load - ZHANG Jian; YANG Jialin; YANG Jie (Renmin Zhujiang)
This paper takes the sluice of the main channel on the east side of East Airport Road, Jinwan Coastal Business District, Zhuhai City, Guangdong Province as an example. Given the wind load on the sluice structure, the paper compares the calculation methods of the design standards in China, the UK, the US, and Japan and analyzes the differences in calculation methods among the four countries. Based on the numerical simulation of computational fluid dynamics, it studies the distribution of wind load on sluice structure in different wind directions, standard wind pressure, and extreme weather such as typhoon. With the structural finite element method, the force characteristics of sluice structure are analyzed under different wind load conditions, which provide some reference for the wind resistance design of sluice structure in coastal areas. The research results show that the wind load value of the Chinese standard considering the wind vibration coefficient is basically the same as that of the UK, the US, and Japanese standards. The wind direction coefficient of the sluice is between 0.75 and 1.03, and the wind load can be multiplied by a certain wind reduction factor according to the angle between the sluice and the dominant wind direction. The shape factor of wind load on the leeward side of the sluice structure is larger than that of general buildings. It is suggested to define the sluice as wind-sensitive building for wind load calculation. Under extreme weather such as typhoons, the wind load of the sluice structure should be multiplied by a certain amplification coefficient considering the wind vibration coefficient, and the stiffness of the sluice structure should be appropriately increased to satisfy the requirements of normal use. Considering the superimposed effect of offshore tide level and storm surge, it is recommended to multiply the bearing capacity of the sluice structure foundation by a safety factor of not less than 1.15.